Interferon Induced Focal Segmental Glomerulosclerosis - Yusuf Kayar; Nuket Bayram Kayar; Nadir Alpay; Jamshid Hamdard; Iskender Ekinci; Sebnem Emegil; Rabia Bag Soydas; Birol Baysal (Case Reports in Nephrology)
Behçet’s disease is an inflammatory disease of unknown etiology which involves recurring oral and genital aphthous ulcers and ocular lesions as well as articular, vascular, and nervous system involvement. Focal segmental glomerulosclerosis (FSGS) is usually seen in viral infections, immune deficiency syndrome, sickle cell anemia, and hyperfiltration and secondary to interferon therapy. Here, we present a case of FSGS identified with kidney biopsy in a patient who had been diagnosed with Behçet’s disease and received interferon-alpha treatment for uveitis and presented with acute renal failure and nephrotic syndrome associated with interferon.